1967
DOI: 10.1002/aic.690130638
|View full text |Cite
|
Sign up to set email alerts
|

Mass and heat transfer from rigid spheres

Abstract: The comments concernin the annular rheometer should also apply to the falling cygnder rheometer since it is essentially an annular flow system with a moving boundary.From the above discussion one may conclude that the method proposed by Swift et al. using the equations developed for the Couette, annular, and falling cylinder rheometers to obtain shear stress-shear rate data is an approximate one in which the accuracy of the results improve as Ri -+ R,. ACKNOWLEDGMENTThe author is indebted to Dr. W. R. Schowalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(51 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…Various correlations ranging from empirical to analytical have been proposed for the estimation of interphase heat transfer coefficient such as Ranz and Marshall (1952), Hughmark (1967), Plesset and Zwick (1954) and Labuntzov et al (1964). In this work, the analytical model of Aleksandrov (1967) is used, which considers both conduction and convection heat transfer, and contains no empirical constants.…”
Section: Interphase Heat Transfermentioning
confidence: 99%
“…Various correlations ranging from empirical to analytical have been proposed for the estimation of interphase heat transfer coefficient such as Ranz and Marshall (1952), Hughmark (1967), Plesset and Zwick (1954) and Labuntzov et al (1964). In this work, the analytical model of Aleksandrov (1967) is used, which considers both conduction and convection heat transfer, and contains no empirical constants.…”
Section: Interphase Heat Transfermentioning
confidence: 99%
“…The two-phase analysis code, TRAC-P1A, uses the correlation proposed by Kelly and Kazimi [17] and MINI-TRAC that by Hori and Toda [18], while CFX-4.2 adapts correlations by Ranz and Marshall [19] and Hughmark [20]. MARS uses Unal-Lahey's correlation as the system code [21].…”
Section: Introductionmentioning
confidence: 99%
“…The empirical constants in Equation (24) are A = 1/2, B = 1/3 and C = 0.6. Hughmark [49] suggested that these constants are valid for the range Re p < 450 and Pr l < 250. …”
Section: Empirical Correlationsmentioning
confidence: 99%